Implementasi Algoritma Profile Matching Dalam Menentukan Penyakit Menular Pada Hewan Sugar Glider - Pieter Octaviandy; Leony Hoki; Robby Wijaya (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
In Indonesia, Sugar Gliders are still not classified as endangered animals, but quotas have been imposed to regulate the capture of Sugar Gliders. The Sugar Glider (Petaurus Breviceps) is a nocturnal marsupial mammal. In addition, Sugar Gliders are often called